2020
DOI: 10.1111/bjd.19132
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy and safety of brodalumab in psoriasis through 120 weeks and after withdrawal and retreatment: subgroup analysis of a randomized phase III trial (AMAGINE-1)

Abstract: Summary Background Brodalumab is efficacious for the treatment of moderate‐to‐severe plaque psoriasis through 52 weeks. Objectives To evaluate the efficacy and safety of brodalumab through 120 weeks, including following withdrawal and retreatment. Methods At baseline, patients were randomized to brodalumab (n = 222) or placebo (n = 220). At week 12, patients achieving a static Physician's Global Assessment (sPGA) score of 0 or 1 (sPGA 0/1) with brodalumab were rerandomized to brodalumab (n = 83) or placebo (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 27 publications
6
43
0
Order By: Relevance
“…Additionally, the rate of arthralgia in the 1-year report was similar to that presented here (0.07 and 0.04 per PY, respectively) [7]. Finally, in a long-term analysis of the AMAGINE-1 trial, rates of arthralgia improved from 11.6% in year 1 to 4.1% in year 3 [5].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Additionally, the rate of arthralgia in the 1-year report was similar to that presented here (0.07 and 0.04 per PY, respectively) [7]. Finally, in a long-term analysis of the AMAGINE-1 trial, rates of arthralgia improved from 11.6% in year 1 to 4.1% in year 3 [5].…”
Section: Discussionsupporting
confidence: 82%
“…Arthralgia was the most common AE listed in the package insert for patients receiving brodalumab for 12 weeks in clinical trials (n = 71; 4.7%) [1]. It was also among the most frequently reported AEs in long-term analyses of AMAGINE-1 (n = 100; 7.5 events per 100 PY) [5] and AMAGINE-2 (n = 295; 9.1 events per 100 PY) [6] and in the 1-year pharmacovigilance analysis (n = 16; 0.07 events per PY) [7]. In this 2-year analysis, there were 73 reports of arthralgia (0.04 events per PY; Table 1).…”
Section: Real-world Occurrence Of Aes Listed In Prescribing Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Papp et al . study reported in this edition of the BJD , 1 a low prevalence of ADA in their patients, suggesting low immunogenicity, may explain the good rates of recapture of response after a period of treatment withdrawal. Low prevalence of ADA associated with biological therapies targeting the IL‐17 pathway (including secukinumab, ixekizumab and brodalumab), has been reported previously 8 .…”
mentioning
confidence: 75%
“…In this issue of the BJD , Papp et al . report a randomized placebo‐controlled trial of the long‐term efficacy of brodalumab through 120 weeks including a successful demonstration of an intermittent treatment regimen 1 …”
mentioning
confidence: 99%